Propagation of coupled Rayleigh-gravity waves on the ocean floor - Vladimir V. Grimalsky; J. Sánchez-Mondragón; Masashi Hayakawa; Svetlana V. Koshevaya; Gennadiy N. Burlak (Geofísica Internacional, 1999)
It is shown that the Ocean-Earth crust interface can propagate gravity-sound Rayleigh waves. Dispersion properties of waves and flux of energy are derived. It is shown that the waves split into low and fast velocity branches. The fast branch has a multimode structure and has a cutoff in frequency and wave number. Numerical solutions are discussed.